Interpretation of Pulmonary Function Tests: A Practical Guide, 2nd Edition - Hyatt, Robert E., Scanlon, Paul D.; Nakamura, Masao (Mayo Foundation for Medical Education and Resea, 2003)
The first edition of Interpretation of Pulmonary Function Tests was well received and met our goal of appealing to a wide, varied audience of health professionals. In the second edition, we added a section to expand our discussion of lung mechanics. We emphasize the mechanical impairments faced by patients with obstructive lung disease and those with pulmonary fibrosis. Three cases were added in which special tests of lung mechanics are informative. The illustrative cases were very popular in the first edition. We have added cases that demonstrate congestive heart failure mimicking pulmonary fibrosis, the importance of recognizing pseudoasthma, the importance of timing of methacholine challenge, the usefulness of measuring the slope of the flow-volume curve, a goiter interfering with inspiratory flow, and several others. We also included several examples in which trend analyses of periodic pulmonary function tests were helpful. The section on bronchial challenge was expanded to cover multiple-dose challenge. The volume exhaled in 6 seconds (FEV6) is introduced as a surrogate for forced vital capacity in obstructive lung disease. Normal predicted values for the 6-minute walk test were added. Recent data from the Lung Health Study on the effect of weight gain on the forced vital capacity and forced expiratory volume in 1 second were included in the obesity section.